JOSHUA AND LONERGAN MEET: Transcendental Precepts and Ethics in the Book of Joshua - Dion, Marie-France; Jamieson, Christine (Science et Esprit, 2023)
This article examines Joshua, chapter one, in light of Lonergan’s transcendental precepts. An ethicist and an exegete team up and investigate how ethical deliberation, on the one hand, and living ‘according to the word of God’ or ‘doing the Torah,’ on the other, share a remarkably similar process for a common purpose.